Development of the Woman-Centred Care Scale- Midwife Self Report (WCCS-MSR) - Deborah L. Davis; Debra K. Creedy; Zoe Bradfield; Elizabeth Newnham; Marjorie Atchan; Lorna Davie; Judith McAra-Couper; Kristen Graham; Christine Griffiths; Linda Sweet; Virginia Stulz (BMC, 2021)
Abstract Background Woman-centred care is recognised as a fundamental construct of midwifery practice yet to date, there has been no validated tool available to measure it. This study aims to develop and test a self-report tool to measure woman-centred care in midwives. Methods A staged approach was used for tool development including deductive methods to generate items, testing content validity with a group of experts, and psychometrically testing the instrument with a sample drawn from the target audience. The draft 58 item tool was distributed in an online survey using professional networks in Australia and New Zealand. Testing included item analysis, principal components analysis with direct oblimin rotation and subscale analysis, and internal consistency reliability. Results In total, 319 surveys were returned. Analysis revealed five factors explaining 47.6% of variance. Items were reduced to 40. Internal consistency (.92) was high but varied across factors. Factors reflected the extent to which a midwife meets the woman's unique needs; balances the woman's needs within the context of the maternity service; ensures midwifery philosophy underpins practice; uses evidence to inform collaborative practice; and works in partnership with the woman. Conclusion The Woman-Centred Care Scale-Midwife Self Report is the first step in developing a valid and reliable tool to enable midwives to self-assess their woman-centredness. Further research in alternate populations and refinement is warranted.